The Effect of Brand Ambassador and Electronic Word of Mouth on Purchasing Decision Scarlett Whitening - Jono Hermanto; Ira Widyastuti; Yasmir Yasmir (JURNAL PENELITIAN EKONOMI DAN AKUNTANSI (JPENSI), 2022)
This research aims to determine the influence of brand ambassador, electronic word of mouth on purchasing decision Scarlett Whitening. The population in this study are all students STIA Setih Setio Muara Bungo used Scarlett Whitening product. The sample in this study was 100 respondents using Non Probability Sampling with purposive sampling. Data collection technique used research questionnaires and the analysis technique is multiple linear regression analysis. The results shown in this study is brand ambassador don’t have a significant effect on purchasing decision Scarlett Whitening and electronic word of mouth have a significat effect on purchasing decision Scarlett Whitening.